Assessment of indigenous community social-economy sustainability using geographical information system - Mustafa, Nordhalia (2019)
The rapid growth of Information and Communication Technology (ICT) as well as a country?s modernization and application of Geographical Information System (GIS) is considered as a way forward to hasten the social-economic development of indigenous communities. An indigenous community in Royal Belum State Park lives in the rural area and refuses to be part of the development intervention. Besides, due to the limited of information about the indigenous community and absence of a large-scale map of their settlements within Royal Belum State Park, infrastructure developments of among them are difficult to identify. It is expected that the latest technology can help the authorities to monitor the development for this community. Thus, this research developed a spatial database system which composed of spatial information and attributes such as demographic information with functioning tool, descriptive analysis and query functions. In the research, User Requirement Analysis (URA) was conducted by distributing the questionnaire to 50 relevant agencies. Spatial data were collected using surveying techniques whereas attribute data were collected using survey form. A database system was developed using GIS software and the web-based system was developed using PHP, JavaScript, HTML, CSS and PostgreSQL. Next, the system was validated using questionnaire distributed to 20 agencies and 30 public users who will use the system. The result showed that 72% (n=36) of respondents strongly agreed and 28% (n=14) of respondents agreed that the web-based system is functioning well and enables data management purpose. As conclusion, the findings have shown that the spatial database can facilitate the assessment of social-economy indicators and providelarger scale mapping for agencies involved in future development planning.